2017
DOI: 10.1111/jce.13256
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular pacemaker lead position is associated with differences in long‐term outcomes and complications

Abstract: Septal pacemaker lead position is associated with a lower mortality compared to apically placed leads, but a higher incidence of atrial fibrillation with higher percentage ventricular pacing. NSNA lead locations are associated with more complications and should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Authors reported that an apical RV lead position was associated with increased mortality compared with a septal position group (31% vs. 24%, p = 0.02). Patients with very high levels of pacing, greater than 90%, had a significantly lower mortality rate in the septal pacing group (16% vs. 31%, p = 0.03), whereas patients with very low levels of pacing, less than 10%, did not have a significant difference in mortality (13% vs. 23%, p = 0.10) [6]. Due to the retrospective design of the present study and the findings of Witt et al [6], none of the aforementioned results can be taken as a definitive answer to the long-debated question of whether an apical position of the RV pacing lead is worse than a non-apical position.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Authors reported that an apical RV lead position was associated with increased mortality compared with a septal position group (31% vs. 24%, p = 0.02). Patients with very high levels of pacing, greater than 90%, had a significantly lower mortality rate in the septal pacing group (16% vs. 31%, p = 0.03), whereas patients with very low levels of pacing, less than 10%, did not have a significant difference in mortality (13% vs. 23%, p = 0.10) [6]. Due to the retrospective design of the present study and the findings of Witt et al [6], none of the aforementioned results can be taken as a definitive answer to the long-debated question of whether an apical position of the RV pacing lead is worse than a non-apical position.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the RV lead position, after adjustment for sex and age at implantation there was no significant association with mortality. Witt et al [6] assessed 3450 unselected patients who underwent DDD PM implantation between 2004 and 2014, among whom the RV lead was positioned at the RV apex in the majority of patients (71.9%) and less commonly at the septum (6.9%) or other RV regions (21.2%). Authors reported that an apical RV lead position was associated with increased mortality compared with a septal position group (31% vs. 24%, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies reporting long‐term outcomes related to HBP showed both acute and chronic increase in His capture thresholds that led to a lead revision in approximately 5% of the population . Nevertheless, irrespective of the anatomical position in the right atrium or right ventricle, lead failure in transvenous conventional pacemakers still represents a relevant clinical problem that occurred in 1‐8% of patients . According to published data 2.4% of patients with cardiac implantable electronic device needed a lead‐related intervention within 6 months after implantation .…”
Section: Discussionmentioning
confidence: 99%
“…e long-term outcomes of this procedure seem to be controversial. Previous studies paid more attention to the number of intracardiac electrodes [2,3], the mode of cardiac pacing (AAI, VVI, and DDD) [2], and the right ventricular pacemaker lead position and their survival differences [2,4,5]. Marchandise et al [3] compared single-lead VDD and DDD pacing and found the overall survival after adjustment was not significantly different in the two groups.…”
Section: Introductionmentioning
confidence: 99%